BRAHMABANDHAB UPADHYAY: A "HINDU-CATHOLIC" HIS SIGNIFICANCE FOR THEOLOGIZING IN INDIA TODAY - STATEMENT OF THE INDIAN THEOLOGICAL ASSOCIATION (Asian Horizons, 2007)
STATEMENTOF THE INDIAN THEOLOGICAL ASSOCIATION Thirtieth Annual Meeting, April 21- 25, 2007 Brahmabandhab Upadhyay (Bhavani Charan Bannerjee)) is an Iridian who has done his country and the faith that he professed, proud. During the 46 years of his life Brahmabandhab Upadhyay (1861-1907) sought the truth relentlessly, engaged in the freedom struggle against foreign domination and lived out Christian discipleship in spite of difficult odds. Equipped with a sharp and probing intellect, he followed truth on a journey that led him to be baptized a Catholic, to appreciate his Hindu upbringing that had made him proficient in Vedanta, to participate in a struggle for freedom that took him to prison and to his death and, finally, to arrive at a fulfillment that is the legacy he leaves to all of us Indians